Regulatory Policy of the Entrepreneurship Development as a Dominant of Economic Security of the National Economy - Вербівська, Людмила Василівна (International Journal of Safety and Security Engineering, 2022)
The regulatory policy of entrepreneurship development is aimed at creating favorable conditions for increasing competitiveness and the role of entrepreneurship in the economic system by applying a set of state regulatory measures aimed at improving the quality of public administration through the formation of a legislative space for the successful functioning and development of entrepreneurship, which, in turn, acts as a dominant economic security of the national economy. The purpose of this article is to study the influence of the regulatory policy of entrepreneurship development on ensuring the economic security of the national economy by determining the level of development of innovative entrepreneurship in the region. An analysis of the state of entrepreneurship in Ukraine was carried out, on the basis of which the main development trends, factors that influenced their formation, as well as directions for improving regulatory policy in the context of ensuring economic security of national security were determined. It has been proven that the focus of entrepreneurial structures on innovative activities will contribute to increasing competitiveness and profitability, which in turn will improve the life of the population, strengthen the economic position of the middle class, and therefore ensure the economic security of the national economy. Within the framework of the article, a methodical approach to the assessment of the development of innovative entrepreneurship in the regions of Ukraine is proposed, which makes it possible to carry out methodologically correct comparisons of the levels of development of the regions at the meso-level both by the complex indicator and by its individual components. The authors grouped and ranked the regions according to a comprehensive indicator and identified the leading regions, regions with an average level of development of innovative entrepreneurship, and outsider regions. Recommendations for overcoming the identified disparities are provided
Keywords: regulatory policy, state regulatory policy, innovative entrepreneurship, economic security, national economy